My bucket list - Keshav Das Joshi (Society of Surgeons of Nepal, 2016)
Son of Ram Das Joshi, Prof Keshav Das Joshi was born at Kathmandu. He completed MBBS on 1968 from Trivandrum Kerela, residency (1970 to 1974) in MS (General Surgery) on 1974 from AIIMS, New Delhi. He served as a registrar on 1975 at Maulana Azad Medical College and training in Clinical Oncology in Tokyo at the National Cancer Hospital) on 1983. He had his training in Plastic Surgery in U.K. 1987 and various periods of training and Observation in Burn & Plastic Surgery in Canada, Belgium, France, Singapore and Switzerland.